2021
DOI: 10.1021/acsnano.1c07275
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment Responsive “Head-to-Foot” Self-Assembly Nanoplatform for Positron Emission Tomography Imaging in Living Subjects

Abstract: Sensitivity and specificity of molecular probes are two important factors in determining the accuracy of cancer diagnosis or the efficacy of cancer treatment. However, the development of probes with high sensitivity and strong specificity still poses many challenges. Herein, we report an 18F-labeled smart tracer ([18F]1) targeting cancer-associated biotin receptor (BR) and self-assembling into nanoparticles in response to intracellular glutathione. The tracer [18F]1 selectively targeted BR-positive cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…This may be attributed to the fact that the dimer formation was much easier and more spontaneous compared to competition with endogenous free cysteine. 33 These in vitro results indicated that the probe [ 18 F]JM-10 could respond quickly to GGT and be reduced by GSH, resulting in an intermolecular condensation reaction to yield the dimer [ 18 F]JM-D in GGT-overexpressed cells (Fig. 3c).…”
Section: Resultsmentioning
confidence: 81%
“…This may be attributed to the fact that the dimer formation was much easier and more spontaneous compared to competition with endogenous free cysteine. 33 These in vitro results indicated that the probe [ 18 F]JM-10 could respond quickly to GGT and be reduced by GSH, resulting in an intermolecular condensation reaction to yield the dimer [ 18 F]JM-D in GGT-overexpressed cells (Fig. 3c).…”
Section: Resultsmentioning
confidence: 81%
“…To date, many bioorthogonal reactions have been developed to design small molecules with the propensity for controlled self-assembly in living cells. One of the pioneering works was reported by Rao and others, in which a biocompatible condensation reaction occurred between 2-cyano-benzothiazole (CBT) and free cysteine (Cys) for specific labeling of terminal cysteine residues in medicinal chemistry. This reaction can proceed smoothly under physiological conditions, with a second-order rate constant of 9.19 M –1 S –1 . Creating a compound bearing both CBT and Cys groups could allow it to condense in cell, forming cyclic dimers/oligomers and subsequently self-assembling into nano/microstructures through hydrophobic and π–π interactions. With the introduction of bio-responsive caging groups on the amino and/or thiol groups, such as enzyme-cleavable bonds and/or disulfide bonds, such a bioorthogonal reaction could be successfully applied to create a target-enabled in situ self-assembly system, which has shown promise for developing various protease-triggered nanoaggregation probes. In our laboratory, this method has also been used to design and synthesize enzyme-responsive small-molecule positron emission tomography (PET) tracers for tumor imaging. …”
Section: Introductionmentioning
confidence: 99%
“…We then synthesized the radioactive tracer [ 18 F]-IR780-1 through a well-established 18 F-exchange reaction between 18 F À and the AMBF 3 group in IR780-1 (Figure 5a). [23] After purification, [ 18 F]-IR780-1 was obtained with a radiochemical purity of ca. 95 % and a specific activity of ca.…”
Section: Methodsmentioning
confidence: 99%